The Effects of Factors on Fund Investment Decisions by Retail Investors in Bangkok Metropolis. - Chirawitbuppa, Maninphapha; Narinthornkul Na Ayutthaya, Arunee; Rittiboonchai, Wisit (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
In this thesis, the researcher investigates (1) the effects of personal factors on the investment decisions of selected Bangkok Metropolis retail investors investing in funds. The researcher also examines (2) the effects of external factors on these investment decisions. The research population consisted of 1,525,170 retail investors in Bangkok Metropolis. Utilizing the purposive sampling method, the researcher selected a sample population of 400 members. Findings are as follows: 1. In regard to the effects of the personal factors on the fund investment decisions made by these retail investors, it was found that the investors paid greatest heed in decision making to the factors of dividend paying policies and persuasion. 2. Insofar as concerns external factors, investment policy was the factor to which investors paid greatest heed. The results of hypothesis testing show that the effects of personal factors on the investment decisions of these retail investors were evinced at a statistically significant level. Article history : Accepted 28 November 2019 SIMILARITY INDEX = 0.00